Análise horária da velocidade do vento referente aos períodos diurno e noturno em localidade litorânea no nordeste do estado do Pará - CONCEIÇÃO, Diemerson Lima da (2019)
Wind is an important meteorological variable, however, little studied in relation to others, such as rainfall, temperature, humidity and radiation. Its importance is highlighted only when situations occur that generate losses for the population, as they occur in the storms. The wind study may also provide subsidies for projects and studies related to architecture, agriculture, hydrology, environment, health, and harnessing wind for power generation. Considering the importance of knowing the daily course of the wind, in this study, wind speed to be analyzed, referring to the day and night periods of months under dry and wet, for the years 2012 and 2013. The study was developed in the coastal ecosystem Experimental Station "Modesto Rodrigues (Latitude: 00º39'45 '' S, longitude: 47º15'56 '' W and altitude of 20 meters)., located in the town of Cuiarana, city of northeastern Pará Salinópolis The wind speed data used to perform this study were measured 15 meters above the ground, in a micrometeorological tower, installed in a pink mango orchard (cv Tommy Atkins) with 15-year-old planted in targeted ranks in the east west direction with spacing of 10 meters between rows and 10 meters between plants. Data schedules mean wind speed were grouped into day amounts refer to the period from 07.00 to 18.00 and the nocturnal values in the period extending from 19:00 to 6:00 a.m., for months as dry (September, October and November) and months rainy (January, February and March). The results showed that the wind speed increased by value from the dawn and extending until around the middle of the afternoon, and again declining more sharply with the dark. It was observed that higher values occurred during the day, reaching a maximum of 4.6 m / s. At night the maximum observed average value was 3.1 m / s. It can also be observed that in the months for the dry season, the wind schedules mean values were higher than in the rainy season. Another finding was that the highest values of the wind intensity occurred in the time between 12:00 and 15:00 hours and the minimum values at night between 00.00 and 04.00.